(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is written based on the memoirs of Kochkor Norqobil, a participant in the Afghan War, writer, and creator. The article describes the experiences and events that the writer witnessed and went through during the Afghan War.